PERLINDUNGAN HUKUM TERHADAP PASIEN SEBAGAI KONSUMEN JASA PELAYANAN KESEHATAN DALAM TRANSAKSI TERAPEUTIK - Andri Pramono; Anggraeni Endah Kusumaningrum (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
The relationship between doctors and patients is a relationship between legal subjects and legal subjects regulated in the rules of civil law which are basically carried out based on mutual agreement, so in this relationship there are rights and obligations that are reciprocal; The doctor's rights are the patient's obligations and the patient's rights are the doctor's obligations. This research is a normative juridical research with an approach to legal principles and legal systematics, namely to find out the applicable principles and identify the main meanings in therapeutic agreement law, legal rights and obligations and legal relationships between patients and doctors and hospital. In therapeutic transactions, there is a relationship between the patient and the health care provider that tends to bring conflict. Many factors cause this conflict, for example, the lack of understanding of the patient's health, the unequal position between the patient and the provider before the law, and the imperfect quality of service delivered by the provider. Judging from the legal standing, therapeutic transactions have far-reaching consequences on a reciprocal basis between patients and doctors.